Population-based comparative analysis of differentially expressed genes between Kashin–Beck disease grades I and II. (3rd May 2016) - Wang, X; Ning, Y; Tan, W; Yu, H; Li, Z; Guo, X
Abstract : Objectives : To identify the differences and similarities of differentially expressed genes in peripheral blood mononuclear cells (PBMCs) between Kashin–Beck disease (KBD) grades I and II. Method : In total, 100 patients with KBD and 100 healthy controls were selected from a KBD endemic area and divided into 100 pairs of KBD vs. controls (50 pairs of patients with KBD grade I and healthy controls, 50 pairs of patients with KBD grade II and healthy controls). RNA was isolated from KBD PBMCs and healthy control PBMCs. Microarray analysis was conducted to identify differentially expressed genes in the different stages of KBD. The microarray data obtained were further confirmed using quantitative real-time polymerase chain reaction (qRT-PCR). Results : In total, eight differentially expressed genes in KBD grade I and 69 differentially expressed genes in KBD grade II were identified. Among these genes, six common genes were differentially expressed in both stages of the disease. The expression ratios of four common genes differed significantly between KBD grades I and II. Based on the expression ratios of the four genes, linear discriminant analysis (LDA) correctly classified the KBD grade (I or II) with 81% accuracy. Conclusions : The similarities and differences of differentially expressed genes in PBMCs of patients with different stages of KBD may play an important role in the pathogenesis of the early phase of KBD. Additionally, six common genes may be considered blood-based genetic biomarkers for the detection and treatment of KBD.